Analisis Strategi Pemasaran Dalam Meningkatkan Minat Peserta Didik Baru di SMA Abdi Pusaka Indonesia - Eva Indah Sari Zebua; Otanius Laia; Maria Magdalena Bate'e; Yupiter Mendrofa (LPPM Universitas HKBP Nommensen, 2024)
This study aims to analyze the marketing strategies implemented at SMA Abdi Pusaka Indonesia, as well as identify factors that influence the interest of new students and formulate more effective marketing strategies. The research method used is qualitative, with an in-depth approach to social and human phenomena. This study found that the marketing strategies currently implemented, such as brochure distribution, visits to junior high schools, and the use of social media, have been running but are not optimal. Factors that influence student interest include the quality of teaching, school promotion, and evaluation and adaptation to the needs of prospective students. To improve marketing effectiveness, schools are advised to develop more structured and interactive social media campaigns, and conduct ongoing evaluations to adjust strategies to the feedback received. Implementing the right marketing strategy can help schools increase the number of applicants and maintain their competitiveness in the education market.